THEORETICAL FRAMEWORK DEVELOPMENT TO STUDY eWAKAF PAHANG ACCEPTANCE: A REVIEW OF THEORIES: Mohammad Zulfakhairi Mokthar, Zarina Kamarozaman, Zuraini Mohamed - Zulfakhairi Mokthar, Mohammad (Qawwam : The Leader's Writing, 2021)
Waqf is one of Islam's oldest and most commonly known charitable giving systems where it has started since 8th century. From then, waqf has evolved from land waqf or immovable property to cash waqf or movable property and recently to online waqf. Online waqf is a term used to describe a donation made by Muslims in the form of money that is made through electronic means (e.g. Internet banking facilities). It helps in improving the collection of waqf funds due to the improvement of internet banking services, as well as a growth in the number of young people who are literate who have access to online transactions which in turn improves the collection of waqf funds. However, the total number of cash waqf collections through online method for Saham Wakaf Pahang is far behind to compare with counter and salary deduction method. Therefore, this study tries to propose a conceptual framework to study demographic factors whether it affects the strength of relationship between the determinants of eWakaf Pahang acceptance. This is a theory adaptation paper where it started with the choosing of theory. The data will be collected through secondary data and analyze using content analysis method to come up with the strongest theory in aspects missing from the domain theory.